Alcalase Microarray Base on Metal Ion Modified Hollow Mesoporous Silica Spheres as a Sustainable and Efficient Catalysis Platform for Proteolysis - Zeng, Qi; Li, Qi; Sun, Di; Zheng, Mingming (Frontiers in Bioengineering and Biotechnology, 2020)
ABSTRACT: The industrial exploitation of protease is limited owing to its sensitivity to environmental factors and autolysis during biocatalytic processes. In the present study, the alcalase microarray (Bacillus licheniformis, alcalase@HMSS-NH2-Metal) based on different metal ions modified hollow mesoporous silica spheres (HMSS-NH2-Metal) was successfully developed via a facile approach. Among the alcalase@HMSS-NH2-Metal (Ca2+, Zn2+, Fe3+, Cu2+), the alcalase@HMSS-NH2-Fe3+ revealed the best immobilization efficiency and enzymatic properties. This tailor-made nanocomposite immobilized alcalase on a surface-bound network of amino-metal complex bearing protein-modifiable sites via metal-protein affinity. The coordination interaction between metal ion and alcalase advantageously changed the secondary structure of enzyme, thus significantly enhanced the bioactivities and thermostability of alcalase. The as-prepared alcalase@HMSS-NH2-Fe3+ exhibited excellent loading capacity (227.8±23.7 mg/g) and proteolytic activity. Compared to free form, the amidase activity of alcalase microarray increased by 5.3-fold, the apparent kinetic constant Vm/Km of alcalase@HMSS-NH2-Fe3+ (15.6 min-1) was 1.9-fold higher than that of free alcalase, and the biocatalysis efficiency increased by 2.1-fold for bovine serum albumin (BSA) digestion. Moreover, this particular immobilization strategy efficiently reduced the bioactivities losses of alcalase caused by enzyme leaking and autolysis during the catalytic process. The alcalase microarray still retained 70.7 ± 3.7% of the initial activity after 10 cycles of successive reuse. Overall, this study established a promising strategy to overcome disadvantages posed by free alcalase, which provided new expectations for the application of alcalase in sustainable and efficient proteolysis.